2022
DOI: 10.3390/genes13081427
|View full text |Cite
|
Sign up to set email alerts
|

An EHPB1L1 Nonsense Mutation Associated with Congenital Dyserythropoietic Anemia and Polymyopathy in Labrador Retriever Littermates

Abstract: In this report, we describe a novel genetic basis for congenital dyserythropoietic anemia and polymyopathy in Labrador Retriever littermates characterized by incidental detection of marked microcytosis, inappropriate metarubricytosis, pelvic limb weakness and muscle atrophy. A similar syndrome has been described in English Springer Spaniel littermates with an early onset of anemia, megaesophagus, generalized muscle atrophy and cardiomyopathy. Muscle histopathology in both breeds showed distinctive pathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…For example, we have cataloged genetic variants from WGS data of nearly 700 dogs across more than 50 breeds, using 2 canine reference genomes ( Lindblad-Toh et al 2005 ; Hoeppner et al 2014 ; Wang et al 2021 ). Ongoing analyses have demonstrated the usefulness of this catalog in identifying genetic variants associated with various Mendelian diseases and traits in our canine companions ( Olby et al 2020 ; Shelton et al 2021 ; Shelton, Minor, Guo, et al 2022 ; Shelton, Minor, Vieira, et al 2022 ). However, unlike humans with the Genome in a Bottle Consortium ( Zook et al 2016 ), we do not have an extensively curated truth set of genetic variants in animal species for validating the accuracy of WAGS.…”
Section: Resultsmentioning
confidence: 99%
“…For example, we have cataloged genetic variants from WGS data of nearly 700 dogs across more than 50 breeds, using 2 canine reference genomes ( Lindblad-Toh et al 2005 ; Hoeppner et al 2014 ; Wang et al 2021 ). Ongoing analyses have demonstrated the usefulness of this catalog in identifying genetic variants associated with various Mendelian diseases and traits in our canine companions ( Olby et al 2020 ; Shelton et al 2021 ; Shelton, Minor, Guo, et al 2022 ; Shelton, Minor, Vieira, et al 2022 ). However, unlike humans with the Genome in a Bottle Consortium ( Zook et al 2016 ), we do not have an extensively curated truth set of genetic variants in animal species for validating the accuracy of WAGS.…”
Section: Resultsmentioning
confidence: 99%
“…During this study, we became aware of an independent effort to investigate the genetic defect in Labrador retrievers with a similar syndrome [ 18 ]. Shelton et al reported the identification of an EHBP1L1 nonsense variant as a likely cause for dyserythropoietic anemia and polymyopathy in this breed [ 58 ]. The fact that two independent truncating variants in the same gene lead to virtually identical and highly characteristic clinical phenotypes in ESSPs and Labrador retrievers provides a further proof for the causality of these variants.…”
Section: Discussionmentioning
confidence: 99%